Birthplace of Brazilians Olympic Swimmers as a Factor of Influence for Sports Success - Bruna Lindman Bueno; Leandro Carlos Mazzei; Larissa Rafela Galatti; Alcides José Scaglia (Revista Intercontinental de Gestão Desportiva, 2020)
Several factors are capable of influencing sports success, including the birthplace of athletes. The Brazilians swimming and marathon have been obtaining good results in the Olympic Games in the last years. Thus, from the delimitation of the population and socioeconomic characteristics of the swimmers' hometown, a more in-depth understanding of the profile of the municipality most likely to form successful swimmers becomes possible. Therefore, the objective of this article is to identify the population and socioeconomic profile of the birthplace of Brazilian Olympic swimmers, providing reflections on the development of high-performance Brazilian swimming. The methodology employed is characterized as quantitative-descriptive, using descriptive statistics for data analysis. From the collection of information about the profile of swimmers' hometowns, the results show that the majority come from municipalities located in the Southeast region of the country, with a population greater than 5,000,000 inhabitants, population density, MHDI, and GDP per-capita high. With these data, it is possible to make more assertive and coherent decisions on the part of sports organizations and managers, in addition to offering more sustainable sports policies and actions to promote swimming and marathon in the long term.